The Effect of Teacher’s Competency, Physical Environment of Classroom and Family Environment Towards Students’ Learning Motivation - Marlina, S; Rahmawati, A; ., Ismiyati (KnE Social Sciences, 2018)
The aim of this research is to know the effect of teacher’s competency, physical environment of classroom, and family environment towards students’ learning motivation. The population of this research was 122 students of grade XI Office Administration Program of SMK in Pekalongan City. The sampling technique used in this research was saturation sampling. The method of data collection used was questionnaire. The analysis data was using multiple regression and descriptive analysis. The research analysis showed (1) there is significant effect of teacher’s competency toward students’ learning motivation (2) there is significant effect of physical environment of classroom toward students’ learning motivation (3) there is significant effect of family environment towards students’ learning motivation This research can be concluded that to improve students’ learning motivation can be achieved by improving teacher’s competency, having better physical environment of classroom, and improving the relationship between family members in family environment. Keywords: Teacher’s Competency, Physical Environment of Classroom, Family Environment, Learning Motivation